PELATIHAN DIVERSIFIKASI OLAHAN IKAN UNTUK PENINGKATAN KETERAMPILAN KELOMPOK USAHA DESA BABULU LAUT KABUPATEN PENAJAM PASER UTARA - Doni Darmasetiadi; Widya Kusumaningrum; Ristiana Eryati; Rafitah Hasanah; Andi Mismawati; Etik Sulistiowati Ningsih (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Babulu Laut Village, located in Babulu Subdistrict, Penajam Paser Utara Regency, East Kalimantan, is a coastal village whose primary catch is milkfish. However, milkfish has not been optimally processed by the community, particularly by the women in Babulu Laut Village. As a result, many of the fish products have low economic value. Therefore, there is a need to diversify fishery products so that milkfish can be enjoyed in various forms that are tasty, nutritious, and have high economic value. The implementation method of this activity began with observation, identification, and training for participants, who are members of small business groups in Babulu Laut Village. The training was conducted using lectures, demonstrations, and documentation related to raw material sorting, additional ingredients, variations in shape and size, frying techniques, and economical packaging techniques.